THE ROLE OF REMOTE DIAGNOSTICS IN MEDICINE. - D.Elmurotova; F.Arzikulov.; Izzatullayev I; Olimov A; Abdurahmonov J (Scholar Express Journals, 2024)
The work presents information about the technology of remote diagnostic systems, highlighting the stages of allowing you to identify various diseases and assess the patient's condition in advance without direct contact with the doctor. The principle and limitations of multichannel cardiography are looked at.
Keywords: Remote diagnostics; multichannel; cardiography; heart